Effects of a basketball intervention on female college students' positive body image: chain mediated role of the experience of embodiment and self-compassion - Zhu, Huachen; Wen, Yuhong (Frontiers in Psychology, 2025)
This study investigated how basketball intervention affects positive body image in female college students, examining the mediating roles of the experience of embodiment and self-compassion. A randomized controlled trial design was adopted, in which forty two participants were randomly assigned to either a 10-week basketball intervention program (conducted twice weekly, each lasting 90 m) or a standard physical education curriculum that included aerobics, Tai Chi, and physical fitness exercises. Data were collected using validated scales measuring the experience of embodiment, self-compassion, body appreciation, and functionality appreciation. The data analysis included repeated measures ANOVA, mediation effect testing, and machine learning models. The basketball intervention produced significant main effects of time, group, and their interaction on the experience of embodiment, self-compassion, and positive body image among female college students. The chain mediation analysis revealed that both the experience of embodiment and self-compassion mediated the relationship between the basketball intervention and positive body image. Specifically, the mediation effects were as follows: the experience of embodiment accounted for 2.73%, self-compassion for 33.61%, and the chain mediation for 11.98%. Participation in both the basketball group and the comparison group was found to enhance the experience of embodiment, self-compassion, and positive body image. However, the basketball intervention produced significantly more pronounced effects compared to the mixed-activity standard physical education program. It directly improved positive body image and also exerted indirect effects through the independent mediating role of self-compassion as well as the sequential mediation of the experience of embodiment and self-compassion.